Enamel pearl diagnosed by cone beam computed tomography: A clinical case report - Beatriz De Carvalho Silva Rocha; Johne Andrade; Claudia Scigliano Valerio; Flávio Ricardo Manzi (Wolters Kluwer Medknow Publications, 2018)
Little research has been performed on tomographic observations of the dental development anomaly known as enamel pearl. This article presents a clinical case report in which enamel pearl was detected through cone beam computed tomography (CBCT). In this study, a patient was referred to undergo a CBCT of the left maxillary molar region, due to the patient's pain symptoms in this region. The CBCT showed the existence of an enamel pearl in tooth 27. A precise diagnosis made it possible for the patient to begin the preventive treatment against periodontal disease in tooth 27.